Dynamic simulation of BTX adsorption in packed bed. (2nd January 2020) - Ncube, T.; Kannan, P.; Al Shoaibi, A.; Srinivasakannan, C.
ABSTRACT: Rigorous design of commercial-scale packed beds accounting multicomponent adsorptions is mathematically complex, often resulting in adopting approximate simplified methods. Hence the present work attempts to simulate adsorption of BTX (benzene, toluene, m xylene) in a packed column of 10 m height and 3 m diameter for two adsorbents namely KIT-6 and mKIT-6 (surface modified) using Aspen Adsorption. The adsorption isotherm data of pure BTX components were generated for the adsorbent using a gas phase gravimetric analyzer. A comparative adsorption capacity indicates adsorption in the following order X > T > B for both the sorbents. m-xylene and toluene performed better on mKIT-6, as a result of which breakthrough and saturation time were higher. An increase in adsorbate feed concentration reduced the breakthrough and saturation time, proportional to the magnitude of increase. A significant reduction in the breakthrough time for benzene and toluene was observed due to competitive adsorption in the case of multicomponent adsorption as compared to pure component adsorption.